Demokrasi Indonesia Masa Kepemimpinan Presiden Jokowi-Amin Periode 2019-2024 - Saiman (Public Administration Dept, Faculty of Social and Political Science, 2023)
Launch of 2020 Indonesian Ombudsman Annual Report on Monday 8 February 2021, President Joko Widodo said